PENGEMBANGAN DESAIN MOTIF KAIN TENUN GOYOR - Noviani, Leny; Wahida, Adam; Thamrin, AG (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The purpose of this program are: (1) to create a design motif of wovenfabric "goyor" more varied; and (2) to make the color composition. The methodused in this program is the training and mentoring. The program is carried outin stages: (1) an increase in knowledge about the importance of developing adesign motif for expanding market segment; (2) provide assistance equipment;(3) training of development product design; and (4) assistance in the form ofconsultancy to the problems faced. Through this program produced three formsof design motifs. Products are finished with attractive colors compositions willincrease the selling price. With the help of tools and capital in the form of asewing machine and materials, the real impact that can be seen is the sustainabilityofthebusiness.